PENGARUH BUDAYA TERHADAP TRADISI NYANDA PADA IBU NIFAS DI DESA CIPINANG KECAMATAN RUMPIN BOGOR JAWA BARAT TAHUN 2018 - Nurul Husnul Lail (Universitas Nasional, 2019)
Background: Based on the results of the IDHS (2012) maternal mortality rate of 359 / 100,000 KH caused by bleeding and infection. And according to MOH (2011) the incidence of uterine subinvolution was 28%. Objective: To find out whether there is an influence of nyanda (immobilization) tradition on postpartum mothers with uterine involution process in Cipinang Village, Rumpin Bogor District, West Java in 2018 Methodology: This study uses Quasi-Experiment Design. This design is two groups, the first group is given nyanda tradition treatment called experiment and the second group is not treated with nyanda tradition called control. Sampling technique: Consecutive Sampling. Research instruments: information sheets for concent, observation sheets, and metlin. The study measured the height of the uterine fundus from days 1 to 4 of postpartum mothers. The population is 44 postpartum mothers and a sample of 40 respondents. Data were analyzed using the Mann Whitney Test because the data distribution was not normal and fulfilled the test requirements. Research Results: Based on the results of the analysis get a value of 0.747 and greater than the value of 0.05. Conclusions and Suggestions: Then there is influence of culture of the nyanda tradition. Nyanda tradition should not be done even though the results of this study have no effect, because nyanda is the same as not mobilization, so that it can affect uterine involution during childbirth.